Uporaba konoplje pri zdravljenju kožnih bolezni - Zagožen, Marjeta (Farmacevtski vestnik, 2019)
Hemp (Cannabis sativa L.) use is becoming increasingly important in medicine. Scientific literature in the area of dermatology presents positive pharmacological effects of cannabinoids in over-secretion of sebum, erythema, pruritus, scleroderma, atopic dermatitis, psoriasis, wonds and skin cancer. The role of cannabinoids in the treatment of the aforementioned diseases is reviewed in the article.
Keywords: Cannabis sativa; Farmakologija; kanabinoidi; Konoplja; Koža; kožne bolezni; vegetabilizirane kovine